METHOD OF ASSESSMENT OF EDUCATIONAL PROCESS RESULTS IN TECHNOLOGICAL EDUCATION. - Yusupov, Mukhammad (Журнал иностранных языков и лингвистики, 2023)
The article describes the technological and methodological evaluation criteria for evaluating the results of the educational process of technological education teachers